Role of ICT Tools in Learning Behaviour of EFL Students - Lamichhane, Sujana (NELTA Bagmati Journal, 2022)
This article explores the various Information and Communication Technology (ICT) tools employed by public schools. The study aims at identifying the ways of using ICT tools and platforms and their role in learning behaviour of secondary level EFL students. ICT, though beneficial for most of the cases, may cause serious problems to the learners if improperly adopted. The study is based on qualitative research design and includes the focus group discussion and classroom observation. The data obtained were transcribed and analysed based on the participant’s perception, experience and classroom observation. Findings indicate both positive and negative aspects of technology induced behavioural changes in the learners. The study suggests that continuous monitoring by school management and parents, regulatory intervention on the irrelevant Internet contents and awareness programmes to the students need to be immediately and effectively administered to stop the learner’s behaviour being negatively affected by ICT.